Peningkatan Hasil Belajar Matematika Siswa Dengan Menggunakan Media Blok Dienes Pada Materi Operasi Penjumlahan Bilangan Cacah - Hermina Manek (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2023)
This study aimed to determine whether the use of Dienes Block as learning media could increase students' mathematics learning outcomes. This research is classroom action research (CAR) which was conducted in 2 cycles. The research was conducted at SDN Bokong 2, Takari District, Kupang Regency in the odd semester of the 2022/2023 school year. The research subjects were 26 students of third grade and a teacher. Data collection instruments in this study included observation sheets, tests, and documentation. The results showed that the use of Dienes Block can improve the mathematics learning outcomes of third grade students of SDN Bokong 2 on the material of the addition operation of whole numbers. It is indicated by the increase and achievement of the minimum criteria for teacher activity, students’ activity, and mathematics learning outcomes of third grade students of SDN Bokong 2 after being taught using dienes block media. The percentage of students who reached the minimum completeness criteria (70) in cycle 2 was 88.5% with a classical average of 84.3. These results improved compared to the learning outcomes of cycle 1 where the percentage of students who reached the minimum completeness criteria was only 38% with a classical average of 69.2.